Analisis Rasio Solvabilitas Untuk Menilai Kinerja Keuangan Pada Perumda Air Minum Tirta Bantimurung Kabupaten Maros - Meldilianus N. J. Lenas; Aminah Aminah (STIM-LPI Makassar, 2022)
This study aims to find out how the financial performance of the Regional Public Company (PERUMDA) Drinking Water Tirta Bantimurung, Maros Regency. The object of this research is the Regional Public Company (PERUMDA) of Tirta Bantimurung Drinking Water, Maros Regency. The data used in this study are primary data and secondary data. The research method uses the library research and field research stages. The method of analysis uses financial ratio analysis. The samples in this study are the balance sheet and income statement of the Regional Public Company (PERUMDA) Drinking Water Tirta Bantimurung, Maros Regency for the 3 year period from 2018 to 2020. The results showed that the company's financial performance as measured by the solvency ratio was good, because the Regional Drinking Water Company, Tirta Bantimurung, Maros Regency was able to fulfill its obligations both short term and long term.